2016
DOI: 10.1063/1.4953257
|View full text |Cite
|
Sign up to set email alerts
|

Paper-based diagnostic devices for clinical paraquat poisoning diagnosis

Abstract: This article unveils the development of a paper-based analytical device designed to rapidly detect and clinically diagnose paraquat (PQ) poisoning. Using wax printing technology, we fabricated a PQ detection device by pattering hydrophobic boundaries on paper. This PQ detection device employs a colorimetric sodium dithionite assay or an ascorbic acid assay to indicate the PQ level in a buffer system or in a human serum system in 10 min. In this test, colorimetric changes, blue in color, were observable with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…For this experiment, we designed a simple microfluidic pattern using Microsoft PowerPoint software (Microsoft, Redmond, WA, USA)3637. The full length of the pattern is 2.8 mm; the circular diameter is 0.4 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this experiment, we designed a simple microfluidic pattern using Microsoft PowerPoint software (Microsoft, Redmond, WA, USA)3637. The full length of the pattern is 2.8 mm; the circular diameter is 0.4 mm.…”
Section: Methodsmentioning
confidence: 99%
“…We printed the pattern on chromatography paper (Grade 1 Qualitative Filter Papers, GE Healthcare Life Sciences, Little Chalfont, Bucks, UK), as shown in Fig. 1 using wax-printer (Phaser 8560 wax printer, Xerox, Norwalk, CT, USA)3637. After baking the paper using the patterned wax at 105 °C for 3 min, hydrophilic-hydrophobic regions formed inside the chromatography paper.…”
Section: Methodsmentioning
confidence: 99%
“…The HEMT biosensor can be used in personal health care products as it is inexpensive, easy to integrate into a portable system, and can be used by anyone without prior training or knowledge. (29) In the future, this technology can pave the way for rapid diagnostics of a panel of CVD biomarkers for better disease risk assessment and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…We then loaded 8 µL of sample onto the test zone and allowed it to rest for 10 min at 25 • C. Detection results were recorded using a digital camera and the signal was analyzed using ImageJ software. The RGB color value of each detection result was obtained, and the R value was used for further calculation [13,36]. We subtracted original test zone background values for each detection result.…”
Section: Performing Origami-based Detection Of Paraquatmentioning
confidence: 99%
“…However, successful detection of multiple analytes using a single PAD relied on maintaining particular, sometimes critical, conditions such as moisture level. In a previous study, we showed that paraquat detection in a PAD required a wet environment [13,36]. Traditional ELISA, however, requires application of multiple reagents, and the time to complete such a process using paper increases the likelihood of any moisture-sensitive components drying out.…”
Section: O-pad For Paraquat Detectionmentioning
confidence: 99%